Anti-Bacterial Activity of Natural Plants on Fish Pathogens Isolated from Different Ponds of Dhaka City (Bangladesh Journal of Microbiology, 2016)
In aquaculture, the incidence of bacterial resistance towards synthetic antibiotics has become a serious problem. Therefore, current research has been focused on detecting the presence of pathogenic bacteria in water bodies and finding a novel therapy against pathogens imparted by the natural products replacing the use of synthetic antibiotics. A total of 10 pond water samples were analysed to determine the pathogenic load employing conventional cultural and biochemical tests. Anti-bacterial activities of natural plants on fish pathogens were determined using the agar-well-diffusion method. All the water samples studied high heterotrophic bacteria counts, which were upto 109 cfu/ml. Among bacterial pathogens, Pseudomonas spp. and Vibrio spp. were found to be present in 6 samples and Aeromonas spp. in 2 samples. The in vitro anti-bacterial activity of the herbal plant extracts against the bacterial pathogens revealed that most of the plant extracts are effective against the pathogenic bacterial isolates.Bangladesh J Microbiol, Volume 31, Number 1-2,June-Dec 2014, pp 9-12